A Project study on Sta. Monica Industries, Inc. - Gutierrez, Emmanuel Y.; Mag-iba, Arlene C.; Matias, Ma. Belinda C.; Navarro, Marilyn Anne L.; Santos, Eric A. (College of Engineering, 1990)
Sta. Monica Industries is a marble manufacturing firm that produces marble tiles (polished and unpolished) and azlar tiles for various uses. The group made several visits to the plant. During these visits, we were able to gather information regarding the firm's production system. Based on our observations, we have enumerated some problem areas that the management can look into. Together with an analysis of these problem ares, we have presented some recommendations that may be considered for implementation if approved. A total of nine problem areas were identified and analyzed. The4se can be classified into the following: layout, safety, production efficiency, and working conditions. The present layout of the workplace does not facilitate smooth traffic in the transport of materials because of the location of the work areas. To minimize intersecting paths, interchanging of the azlar production workplace and the polishing workplace is recommended. Another problem on the layout is the absence of a permanent storage area for finished tiles. It may be placed beside the delivery area for better accessibility. Four problem areas deal with safety considerations. It was found out that marble mud covered the floor of the workplace. The marble mud can be slippery and may pose danger to the workers. The canals, where the water from the slicer flows, are left uncovered. This can cause the possibility of a worker falling into it. It is recommended that the cleaning of the workplace be the responsibility oft he utility men. This can be done using a simple "walis tingting". For the canals, a steel grill can be made as cover. Another safety concern is the noise level the workers are exposed to. It exceeds the specified level by the Philippine Safety Organization. To prevent too much exposure to high noise level, ear plugs should be worn by the workers as a protection. The workers, also, do not wear the specified equipment. However, these equipments are provided for by the company. The workers should, therefore, be constantly reminded to wear them. Posters should be hung around the workplace where thew workers can always see them. The plank used by the workers carrying the slab is too narrow and unstable to walk on. An inclined ladder with a width of at least 28 in. or 70 cm. would be safer. On production efficiency, there were two problem areas. In the slicing operation, the slabs are broken off into smaller parts. The dimensions of these parts are not uniform. Therefore, scraps are created. To minimize scrap, the slab should be divided to just two parts. In the transport of the marble blocks, on the other hand, a winch is utilized to lift the blocks from the storage area to the carriage. A crane is proposed as an alternative for more efficient transfer of the blocks. Lastly, another problem area on working conditions was identified. The polishing table was too low for the workers. The table's height can be adjusted to about 97 cm. to minimize the bending required for workers. Production planning and control will be discussed in detail in the report.